2011
DOI: 10.1371/journal.pone.0019513
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of Epidemic Neisseria meningitidis Serogroup X Meningitis in Togo and Burkina Faso

Abstract: Serogroup X meningococci (NmX) historically have caused sporadic and clustered meningitis cases in sub-Saharan Africa. To study recent NmX epidemiology, we analyzed data from population-based, sentinel and passive surveillance, and outbreak investigations of bacterial meningitis in Togo and Burkina Faso during 2006–2010. Cerebrospinal fluid specimens were analyzed by PCR. In Togo during 2006–2009, NmX accounted for 16% of the 702 confirmed bacterial meningitis cases. Kozah district experienced an NmX outbreak … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
97
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(100 citation statements)
references
References 18 publications
1
97
0
2
Order By: Relevance
“…Polyvalent vaccines, including MenW glycoconjugate, are currently produced and used in developed countries and could potentially be mobilized for use in Africa. In contrast, although the need for a vaccine against serogroup X Neisseria meningitidis has been recognized for many years (4,5,14,15), none is currently available.…”
mentioning
confidence: 99%
“…Polyvalent vaccines, including MenW glycoconjugate, are currently produced and used in developed countries and could potentially be mobilized for use in Africa. In contrast, although the need for a vaccine against serogroup X Neisseria meningitidis has been recognized for many years (4,5,14,15), none is currently available.…”
mentioning
confidence: 99%
“…The bactericidal depletion assay using strain 9557 revealed that the key antigens responsible for the bactericidal activity were the L8 LOS, PorA (P1.19 epitope), OpcA, and fHbp-1. While the strains assayed in this study have ST-5403, the majority of strains responsible for the serogroup X N. meningitidis epidemic and carriage in Africa have either ST-181 or ST-751 (3,8,21). The serogroup X N. meningitidis strains that have ST-181 or ST-751 differ in their PorAs from the ST-5403 N. meningitidis strains: their OpcA and LOS immunotype is not known, but they do express fHbp-1, like the ST-5403 N. meningitidis strains.…”
Section: Resultsmentioning
confidence: 97%
“…caused by strains belonging to the same cc (ST-5 cc) and expressing the same PorA (P1. 20,9) which is included in our A-OMV [10,47,48]. The antigenic variation among outer membrane proteins is less studied for MenW strains, nonetheless most MenW strains isolated since 2002 have been caused by ST-11 strains expressing PorA P1.5,2 [10,47,48] such as the MenW vaccine strain used here.…”
Section: Prospects For a Trivalent Awx Vaccinementioning
confidence: 99%
“…The first, large MenX outbreak was reported in Niger in 2006, with a seasonal incidence of 28 per 100,000 [7]. MenX outbreaks were also reported in Kenya and Uganda in 2006 [8], Togo in 2007 and Burkina Faso in 2010 [9]. Whereas the majority of the MenX cases have been reported from West Africa and caused by strains belonging to sequence type (ST) 181 clonal complex (cc) [10], the Kenya/Uganda outbreak was caused by MenX ST-5403 strains genetically distinct from ST-181 strains.…”
Section: Introductionmentioning
confidence: 99%